Perceptions about the cultural practices of male partners during postpartum care in rural Tanzania: a qualitative study. Issue 1 (1st January 2017) - Reuben Mahiti, Gladys; Mbekenga, Columba K.; Dennis Kiwara, Angwara; Hurtig, Anna-Karin; Goicolea, Isabel
ABSTRACT: Background : Men play an important role in maternal health. The postpartum period is a critical stage, yet there is a scarcity of research that explores men's involvement during this stage. Objective : The aim of the study was to explore male partners' perceptions of the cultural practices during postpartum care in rural Tanzania. Methods : Fourteen focus group discussions were conducted with 93 men, with an age range of 19–65 years, in August 2013. The study was conducted in the Kongwa District, located in the Dodoma region in central Tanzania. Qualitative data were digitally recorded, transcribed verbatim and analyzed using content analysis. Results : Four categories emerged, namely: 'Men as providers and, occasionally, care takers', 'Men as decision makers', 'Diverse perceptions of sexual abstinence' and 'Barriers for men in using/accompanying partners to use reproductive and child healthcare services'. The cross-category theme 'Men during postpartum: remaining powerful but excluded' refers to how men are in a powerful position above women in different aspects of life. Elderly women played an important role in caring for postpartum mothers and their newborns, but men were the ones making the final decision about where to seek care. Traditional practices isolated men from their partners for a certain period, and enforced sexual abstinence for the women during the postpartum period. However, cultural norms permitted men to engage in extramarital relations. Reproductive and child healthcare services were perceived by men as not welcoming the male partners, and local gender norms discouraged men from accompanying their partners to seek services. Conclusions : In this study, we found that men perceived their role during the postpartum period as financial providers, decision makers and, occasionally, care givers. Men also held diverse perceptions with regard to sexual abstinence and felt excluded from participating in maternal healthcare services.